Emotion regulation strategies and mental health symptoms during COVID-19: the mediating role of insomnia - Justyna Mojsa-Kaja; Zorana Ivcevic (International Journal of Occupational Medicine and Environmental Health, 2022)
Objectives COVID-19 has become a major source of stress for people around the world. Stressful life events play a role in the pathogenesis of sleep disorders such as insomnia which is considered a risk factor for anxiety and depression. Emotion regulation is an important factor linked with sleep and mental health problems. Therefore, the main goal of the present study was to examine whether insomnia could constitute a mediation mechanism that explains the relationship between emotion regulation strategies (rumination, reappraisal, suppression) and stress-induced mental health outcomes during the COVID-19 pandemic.